Употребление синтетических и аналитических форм степеней сравнения прилагательного в современном английском языке - Пиесарскас, Б. (Kalbotyra, 1962)
The spheres of the use of synthetical (or inflectional) and analytical (or periphrastic) comparison of adjectives are explained by the tendency of the English language to a shorter form of a word. Synthetical comparison is regularly used with adjectives which remain practically dissyllabic after the suffixes -er, -est are added (if the adjective becomes trisyllabic the vowel in the unstressed middle syllable is reduced to a mere glide); all other adjectives regularly take analytical forms. There is, however, a complex interpenetration of the use of the two modes of comparison. Especially frequent are instances of the use of analytical comparison with adjectives belonging to the sphere of synthetical comparison, which are analysed at length in the present article. The preferrence of analytical comparison is determined by several factors, namely, structural (the chief factor), phonetical and semantical. Synthetical comparison is sometimes used with adjectives belonging to the sphere of analytical comparison in order to bring about certain stylistic effects.